Online marketing assistance with e-commerce at UKM Athaya Kitchen Semarang - Rizky Muliani Dwi Ujianti; Iffah Muflihati; Noora Qotrun Nada (Community Empowerment, 2022)
Breastfeeding mothers currently need food to facilitate breast milk so that babies get good nutrition and prevent stunting. The partner of this PKM activity is UKM Athaya Kitchen. To market their products sustainably, partners need e-commerce. This PKM program is carried out at UKM Athaya Kitchen by developing e-commerce, training, and mentoring in selling with e-commerce. The results of this program are the establishment of e-commerce for selling the the milkyflow breastfeeding biscuits, increasing the ability and knowledge of partners in using e-commerce. In addition, it can increase their marketing reach to be more comprehensive; more products sold so that the partner's economy will improve.